Optimalisasi Pelayanan Haji Ramah Lansia Pada Kantor Kementerian Agama Provinsi Maluku - Tamheryaan, Abu S.L; Tuanaya, Wahab; Rolobessy, Mike J. (LPPM Institut Pendidikan Nusantara Global, 2024)
In support of the service of Hajin Ramah Lansia and many jamaah by 2023, there is a need for optimization of the services of Lansia Ramah Haji at the Office of the Ministry of Religion of Maluku Province. The research method used is qualitative descriptive by conducting direct interviews with the chosen informants. As for the research is as follows: (1). (2) The accommodation has been fully prepared by the Kanwil Kemenag Maluku which is the Hajj hostel building in the village of Waiheru with a total of 120 rooms and 673 beds and in one bed can accommodate 6 to 7 Jemaah Hajj. (3) Health services are always carried out by the Government of the province of Maluku to the entire Hajj community and the more priority is the elderly and those with special needs.